Fourth generation evaluation: assisting family members of crack cocaine users - Maria de Lourdes Custódio Duarte; Leticia Passos Pereira; Agnes Olschowsky; Juliana de Carvalho (Universidade Federal de Santa Maria, 2019)
Objective: To know the evaluation of professionals of a Psychosocial Support Center III (CAPS) on the care provided to relatives of crack cocaine users. Method: Qualitative study, with reference to the Fourth Generation Evaluation. Data were collected from June to September 2013, with 15 CAPS professionals, through interviews and observations, with analysis by the constant comparative method, originating the thematic axis Care provided to family members of crack cocaine users. Results: Care provided to the families was evaluated as paramount in the treatment process, considering individual care, family group, home visits, and welcoming as relevant spaces. Final considerations: We perceived the importance of heterogeneous spaces for family inclusion in substitutive services, in addition to the professionals' need to further qualify the care provided to these families